Staging surgery in early-stage ovarian mucinous tumors according to expansile and infiltrative types - Sebastien Gouy; Marine Saidani; Amandine Maulard; Matthieu Faron; Slim Bach-Hamba; Enrica Bentivegna; Alexandra Leary; Patricia Pautier; Mojgan Devouassoux-Shisheboran; Catherine Genestie; Philippe Morice (Elsevier, 2017)
The aim of this study is to determine the value of surgical staging for the two histologic types (expansile or infiltrative) of apparent stage I mucinous ovarian carcinoma. We retrospectively analyzed patients treated from 1976 and 2016 for apparent macroscopic stage I ovarian mucinous carcinoma. Extra-ovarian disease and tumors that metastasized to the ovaries were excluded. Two expert pathologists performed pathologic reviews of tumor data, according to 2014 WHO classification criteria. Tumors were typed as expansile or infiltrative and clinical and histologic characteristics were studied. The value of staging procedures (peritoneal and nodal) was based on the rate of microscopic involvement in macroscopically normal specimens. Of 114 cases reviewed, 46 were excluded (26 with macroscopic stage > I; 20 inaccessible for pathologic review). Of 68 patients included, 29 had expansile and 39 had infiltrative types. 27 patients received one-step surgery and 41 received restaging surgery. 52 patients received "complete" peritoneal surgical staging (including cytology, peritoneal biopsies, and an omentectomy or large omental biopsies). 24 underwent appendectomies and 31 underwent lymphadenectomies (8 expansile and 23 infiltrative). Before histologic analyses of staging specimens, 35 had "initial" stage IA and 33 had IC disease. After histologic analyses of lymph nodes, 4 cases (17%, all infiltrative) had nodal involvement, and 2 showed microscopic peritoneal disease (1 omentum and 1 right diaphragm peritoneum). Three patients were upstaged based on isolated positive peritoneal cytology. To conclude, peritoneal staging procedures are required for both types of mucinous ovarian carcinoma. Lymphadenectomy could be omitted in expansile, but required in infiltrative type.